Hyperpolarized functional magnetic resonance of murine skeletal muscle enabled by multiple tracer-paradigm synchronizations. - Avigdor Leftin; Tangi Roussel; Lucio Frydman (PLoS ONE)
Measuring metabolism's time- and space-dependent responses upon stimulation lies at the core of functional magnetic resonance imaging. While focusing on water's sole resonance, further insight could arise from monitoring the temporal responses arising from the metabolites themselves, in what is known as functional magnetic resonance spectroscopy. Performing these measurements in real time, however, is severely challenged by the short functional timescales and low concentrations of natural metabolites. Dissolution dynamic nuclear polarization is an emerging technique that can potentially alleviate this, as it provides a massive sensitivity enhancement allowing one to probe low-concentration tracers and products in a single-scan. Still, conventional implementations of this hyperpolarization approach are not immediately amenable to the repeated acquisitions needed in real-time functional settings. This work proposes a strategy for functional magnetic resonance of hyperpolarized metabolites that bypasses this limitation, and enables the observation of real-time metabolic changes through the synchronization of stimuli-triggered, multiple-bolus injections of the metabolic tracer 13C1-pyruvate. This new approach is demonstrated with paradigms tailored to reveal in vivo thresholds of murine hind-limb skeletal muscle activation, involving the conversion of 13C1-pyruvate to 13C1-lactate and 13C1-alanine. These functional hind-limb studies revealed that graded skeletal muscle stimulation causes commensurate increases in glycolytic metabolism in a frequency- and amplitude-dependent fashion, that can be monitored on the seconds/minutes timescale using dissolution dynamic nuclear polarization. Spectroscopic imaging further allowed the in vivo visualization of uptake, transformation and distribution of the tracer and products, in fast-twitch glycolytic and in slow-twitch oxidative muscle fiber groups. While these studies open vistas in time and sensitivity for metabolic functional magnetic resonance studies in muscle, the simplicity of our approach makes this technique amenable to a wide range of functional metabolic tracer studies.